Effect of Nanoconfinement of Polyphenolic Extract from Grape Pomace into Functionalized Mesoporous Silica on Its Biocompatibility and Radical Scavenging Activity - Ana-Maria Brezoiu (Antioxidants, 2020)
The aim of this paper is to assess the properties of Mamaia (MM) grape pomace polyphenolic extract loaded onto pristine and functionalized MCM-41 mesoporous silica as potential ingredients for nutraceuticals or cosmetics. The chemical profile of hydroalcoholic polyphenolic extracts, prepared either by conventional extraction or microwave-assisted method, was analyzed by reverse-phase high-performance liquid chromatography with photodiode array detector (HPLC-PDA) analysis, while their radical scavenger activity (RSA) was evaluated using DPPH (2,2-diphenyl-1-picrylhydrazyl radical) and ABTS (2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) assays. The extract-loaded materials were characterized by Fourier transform infrared (FTIR) spectroscopy, N2 adsorption-desorption isotherms, thermogravimetric analysis, as well as RSA (DPPH and ABTS assays). The polyphenols release profiles from pristine and functionalized (with mercaptopropyl, propyl sulfonic acid, cyanoethyl and propionic acid moieties) MCM-41-type supports were determined in phosphate buffer solution (PBS) pH 5.7. For selected materials containing embedded phytochemicals, cellular viability, and oxidative stress level on immortalized mouse embryonic fibroblast cell line (NIH3T3) were evaluated. A more acidic functional groups linked on silica pore walls determined a higher amount of phytochemicals released in PBS. The extract-loaded materials showed a good cytocompatibility on tested concentrations. The embedded extract preserved better the RSA over time than the free extract. The polyphenols-loaded MCM-41-type silica materials, especially MM@MCM-COOH material, demonstrated a good in vitro antioxidant effect on NIH3T3 cells, being potential candidates for nutraceutical or cosmetic formulations.